2015
DOI: 10.1007/s12253-014-9884-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional Variants of Lipid Level Modifier MLXIPL, GCKR, GALNT2, CILP2, ANGPTL3 and TRIB1 Genes in Healthy Roma and Hungarian Populations

Abstract: The role of triglyceride metabolism in different diseases, such as cardiovascular or cerebrovascular diseases is still under extensive investigations. In genome-wide studies several polymorphisms have been reported, which are highly associated with plasma lipid level changes. Our goal was to examine eight variants: rs12130333 at the ANGPTL3, rs16996148 at the CILP2, rs17321515 at the TRIB1, rs17145738 and rs3812316 of the MLXIPL, rs4846914 at GALNT2, rs1260326 and rs780094 residing at the GCKR loci. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Moreover, TRIB1 rs17321515 A allele could affect the serum lipids levels such as FPG, HDL, and TC in each group. Our conclusion is consistent with the previous studies which were conducted in other countries [26, 43, 45].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, TRIB1 rs17321515 A allele could affect the serum lipids levels such as FPG, HDL, and TC in each group. Our conclusion is consistent with the previous studies which were conducted in other countries [26, 43, 45].…”
Section: Discussionsupporting
confidence: 94%
“…In a Chinese Han cohort study, TRIB1 rs17321515 AA genotype carriers had higher TG level than GG genotype carriers [42]. Katalin et al also found that TRIB1 rs17321515 AA genotype carriers had higher serum TG and TC levels than GG + GA genotypes carriers [43]. In consideration of the higher mortality rate of NAFLD-related CHD than the single liver disease, it is meaningful to investigate the effect of TRIB1 rs17321515 gene polymorphism on the risk of CHD in general population and NAFLD patients, and the effect on the serum lipids levels [4, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Besides these three SNPs loci, rs12130333 was closely associated with the Fredrickson hyperlipoproteinemia type 5, characterized by a mixed hyperlipidaemia of elevated levels of VLDL and CM [ 36 ]. On the contrary, rs2131925 was shown to be associated with a mean reduction in plasma TG of 4.94 mg/dl [ 37 ], and the patients carried rs12042319 was also presented lower LDL-C and TG levels [ 38 ]. Another exon sequencing result of the 7 exons of a multi-ethnic sample of 3551 individuals in the Dallas Heart Study provided evidence for a link between the ANGPTL3 gene variant and plasma TG levels.…”
Section: The Population Studies Of Angptl3 Gene Variants In Humansmentioning
confidence: 99%
“…Despite the fact that today's Hungarian Gypsies have genetic variants typical of India and Europe, the two populations fundamentally differ from each other in their genetic architectures [4,5]. Recent genetic epidemiological studies also indicated significant genetic differences between the Hungarian general (HG) and Hungarian Roma (HR) populations [6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%